Necrotizing pancreatitis after removal of prophylactically placed pancreatic stent - Sundaram, Sridhar (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Sundaram S. Necrotizing pancreatitis after removal of prophylactically placed pancreatic stent. Turk J Gastroenterol 2019; 30(10): 928-9.